Intercropping of plantains with food crops: maize, cassava and cocoyams - Devos, P.; Wilson, G.F. (1979)
Data on growth, yields, labour requirements and costs are tabulated for growing plantains as a sole crop and intercropping them with cocoyam, and at normal or low planting densities with maize and cassava. Yields were not depressed by any of the intercrop combinations, but cassava yields were not sufficiently high to compensate for the extra labour requirement. Results suggested that intercropping with maize alone, with plantain at a normal but not low planting density, might be feasible. Intercropping with cocoyam resulted in high returns for both crops with relatively low labour input and production costs, and is recommended. Some of the most common crop combinations involving plantain were compared with plantain in sole cropping. Plantain bunch weights were not suppressed when the other crops were cocoyam, and combinations of maize and cassava. Reducing plantain population to accomodate other crops adversely affected economic returns. The plantain-cocoyam combination had a low labour input and the highest return. The poor performance of cassava suggests that it is not suited to cropping combinations with plantain.